Studi Kelayakan Usaha Grosir Ayam Ras pada Usaha Bapak Bronza Pekanbaru) - Misral Misral; Hendri Ali Ardi; Dedi Dermawan; Denur Denur (Jurnal Teknik Industri Terintegrasi, 2022)
Chicken is a basic need of the people in everyday life. as a basic need, chicken hasa high amount of demand. Therefore, it becomes a high business opportu nity. From the existing broiler chicken business owned by Mr. Brozan, the researcher analyzed the feasibility study of the business. The feasibility study carried out is the feasibility of the market aspect and the feasibility of the financial aspect. The results of the analysis show that Mr. Brozan's business is declared feasible based on a feasibility study, and from the financial aspect, the sensitivity analysis shows that if there is a price increase or stock restrictions from livestock, the business is still declared financially feasible.